2006
DOI: 10.1103/physrevb.73.073108
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and energetics ofBxCyNzlayered structures

Abstract: We investigate the relative stability and electronic structure of several B x C y N z layered structures using first-principles calculations. The twenty structures we considered are derived from a graphite layer by placing carbon, nitrogen, or boron atoms on each site. Interestingly, a structure with B 3 C 2 N 3 stoichiometry was found to be more stable than the eight BC 2 N structures in our study. The BCN compositions we considered present a wide range of electronic behaviors. In general, we observe that str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(75 citation statements)
references
References 24 publications
6
69
0
Order By: Relevance
“…This model of (B 3 N 3 ) x (C 6 ) 1−x captured the main feature of these heterostructures. As shown by previous works [11,12], both stoichiometry and geometry change the band gap of B-C-N nanotube. The maximum band gap is achieved at B/N ratio of 1.…”
Section: Modeling and Computational Detailsmentioning
confidence: 76%
See 2 more Smart Citations
“…This model of (B 3 N 3 ) x (C 6 ) 1−x captured the main feature of these heterostructures. As shown by previous works [11,12], both stoichiometry and geometry change the band gap of B-C-N nanotube. The maximum band gap is achieved at B/N ratio of 1.…”
Section: Modeling and Computational Detailsmentioning
confidence: 76%
“…By varying h-BN concentration x, the domain size effect on mechanical properties of mono-layer hexagonal BNC heterostructures can be appropriately presented in our (B 3 N 3 ) x (C 6 ) 1−x model. We need to emphasis that although we only investigated the effect of stoichiometry of h-BN here, this domain model is different from point model of B x C y N z model at x = z where hexagonal (B 3 N 3 ) structure is not considered [11]. In other words, our model specified not only the stoichiometry of B/N ratio of 1, but also the hexagonal (B 3 N 3 ) and C 6 structures, to represent the two separated phases in heterogeneous h-BNC structures.…”
Section: Modeling and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, theoretical and experimental investigations have indicated that visible light absorption and emission with tuneable wavelength can be achieved by controlling the carbon content in (B, N) rich BCN nanostructures, which then can be considered as metal-free light energy converters [33][34][35]. However, the study on this family of ternary photocatalysts is rather rare, although such materials fulfil basic requirements of photocatalysts, including being stable, visible-light responsive, and inexpensive.…”
Section: Science China Materialsmentioning
confidence: 99%
“…The structural similarity between graphene (G) and h-BN motivates the alloying of the two to achieve ternary hexagonal boron-carbon-nitride (h-BC x N) composite with tunable electronic properties [5][6][7][8][9][10][11] . However, the ability to undergo homophilic (C-C) as well as heterophilic (C-B, C-N and BN) in h-BC x N generates a rich variety of polymorphic structures, making the precise control of their chemical stoichiometry and geometry formidable.…”
mentioning
confidence: 99%